Genotype and Sex Effect on Gastrointestinal Nutrient Content, Microflora and Carcass Traits in Nigerian Native Chickens - Peters, Sunday O.; Idowu, Olusegun M.O.; Agaviezor, Brilliant O.; Egbede, Raphael O.; Fafiolu, Adeboye O. (International Journal of Poultry Science, 2010)
The nutrient concentration of crop and gizzard contents of three genotypes of indigenous scavenging chickens under rural conditions were investigated along-side with the micro-flora community of the Gastrointestinal Tract (GIT), body dimensions and carcass traits. Genotype significantly (p